Exosomes derived from M2 macrophages induce angiogenesis to promote wound healing - Lyu, Leifeng; Cai, Yuanqing; Zhang, Guangyang; Jing, Zhaopu; Liang, Jialin; Zhang, Rupeng; Dang, Xiaoqian; Zhang, Chen (Frontiers in Molecular Biosciences, 2022)
There is an urgent clinical need for an appropriate method to shorten skin healing time. Among most factors related to wound healing, M2 macrophages will be recruited to the wound area and play a pivotal role in a time-limiting factor, angiogenesis. The exploration of exosomes derived from M2 in angiogenesis promotion is an attractive research field. In this project, we found that exosomes from M2 (M2-EXO) promoted the angiogenic ability of HUVECs in vitro. With a series of characteristic experiments, we demonstrated that M2-EXO inhibited PTEN expression in HUVECs by transferring miR-21, and further activated AKT/mTOR pathway. Then, using a full-thickness cutaneous wound mice model, we demonstrated that M2-EXO could be used as a promotor of angiogenesis and regeneration in vivo. Furthermore, M2-EXO-treated skin wounds exhibited regeneration of functional microstructures. These results demonstrate that M2-EXO can be used as a promising nanomedicine strategy for the therapeutic exploration of skin healing with the potential to be translated into clinical practice.